Analysis of the Influence of Transmission Systems and Vehicle Weight on the Range Capability of the Mandalika Desantara Prototype Vehicle (Mechanical Engineering Department Universitas Buana Perjuangan Karawang, 2025)
The development of electric vehicles (EVs) plays a vital role in reducing carbon emissions and decreasing dependence on fossil fuels. This study examines the range efficiency of the Mandalika Desantara electric prototype by investigating the impact of vehicle weight and transmission configuration on energy consumption. Experimental tests were conducted using three different vehicle weights (120.5, 130.5, and 140.5 kg) and multiple transmission ratios. The results indicate a positive correlation between vehicle weight, energy usage, and travel performance. The lowest energy consumption was recorded at 21.33 Wh for the 120.5 kg configuration, achieved at an average speed of 14.42 km/h. The highest was 46 Wh for the 140.5 kg configuration, attained at 20.00 km/h. Motor power output ranged from 113.01 W to 177.22 W, with a range efficiency varying between 0.052 km/W and 0.113 km/W. Travel times ranged from 548 seconds at a transmission ratio of 6.43 to 822 seconds at a ratio of 10.29. These findings underscore the importance of optimized weight management and transmission selection in enhancing EV performance, thereby contributing to the development of more energy-efficient and sustainable electric mobility solutions.